Energy input effects on the microstructure and mechanical behavior of Ti–Nb alloy additivelymanufactured by electron beam melting - Grubova I. Yu. Irina Yurievna; Kozadayeva M. Maria; Khrapov D. Dmitriy; Rybakov V. A. Vladimir Andreevich; Sharonova A. A. Anna Aleksandrovna; Surmenev R. A. Roman Anatolievich; Koptyug A. V. Andrey; Tyurin A. Alexander; Korost D. V. Dmitry; Rasposienko D. Yu. Dmitriy; Makarov V. V. Vladimir; Surmeneva M. A. Maria Alexandrovna (2025, 2025)
Title screen